If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying e(-6w) = 95 Remove parenthesis around (-6w) e * -6w = 95 Reorder the terms for easier multiplication: -6e * w = 95 Multiply e * w -6ew = 95 Solving -6ew = 95 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Divide each side by '-6w'. e = -15.83333333w-1 Simplifying e = -15.83333333w-1
| e^2=95 | | 3+7k=5k-7 | | 4x+12y=62 | | -97=5(1-7a)+3 | | 4x-8=4x+3 | | X+.05X=119.95 | | -7x-7x=56 | | -14+3n=4(n-3) | | 2x-18=6(7-3x) | | 7+22x+3x^2=0 | | 12z-4=11z+4 | | -7x+7x=56 | | 8(1-3n)=-112 | | 9r(r+5)= | | 25q-(25q+40000)=0 | | 63x^4+126x^3+35x^2=0 | | 4+3n=20+7n | | =-0.3x^2+3x+4 | | 8x-(6-2x)=2x-6 | | G(x)=-0.3x^2+3x+4 | | m^2+4.5m-2.5=0 | | 7x+9=-103 | | 2x+11=65 | | xsquared-30x+50=0 | | 5i=4(5x-2u) | | 1-4x=-6x-17 | | 2=6y | | 18x-8=16x+8 | | (7v^2-4v-6)+(5v^2-3v+2)= | | 14x^4-6x^3+2x^2=0 | | 2xsquared+7=4x | | 8.35x+58.45=116.9 |